An Analysis of Positive Politeness Strategies in Alex Kurtzman Film “People Like Us” - Herlina, Herlina (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2017)
People normally behave in accordance with their hope concerning their public self-image or face wants to be respected. Face means public self-image of a person; it refers to the emotional and social sense of self that everyone has and expects everyone to recognize (Yule, 2010). Face has two aspects, positive and negative. An individual’s positive face is reflected in his or her desires to be liked, approved of, respected of and appreciated by others. While an individual’s negative face is reflected in the desire not be impeded or put upon, to have the freedom to act as one chooses (Thomas, 1995:169). Therefore, people in their relationship need to preserve both kinds of faces for themselves and the people they interact with the politeness utterances. Considering the phenomena above, the speaker should be able to produce the suitable politeness strategy for being considered as a polite person. Furthermore, the writer is attracted to analyze the politeness strategies based on Brown and Levinson’s politeness strategy in a film. The film entitled “People Like Us” has a good solid story of a young man dealing with both his family and keeping his job. The story puts the situation most in a public area, where the different statuses such as family, friend, client, boss or the superior interact as the result there are many politeness strategy employed in this movie. The writer found out there are 15 strategies of positive politeness strategies based on Brown and Levinson. All the kinds of those strategies are employed by the main characters in the Alex Kurtzman film People Like Us. Namely notice, attend to hearer; exaggerate; intensify interest to the hearer; use in-group identity markers; seek agreement; avoid disagreement; presuppose/rise/assert common ground; joke; assert or presuppose S’s knowledge of and concern for H’s wants; offer, promise; be optimistic; include both the speaker and the hearer in the activity; give (or ask for) reason; assume or assert reciprocity; give gift to the hearer. Furthermore, it is discovered that there are two factors, namely payoff and circumstances that influence the employment of positive politeness. By knowingKeywords : analysis, positive politeness strategies, face, pragmatics